Highly nutritious diet resists Salmonella Typhimurium infections by improving intestinal microbiota and morphology in broiler chickens - He, Yang; Yang, Yanyan; Dong, Yuanyang; Ito, Koichi; Zhang, Bingkun (Poultry science, 2020)
Salmonella Typhimurium (S. Typhimurium) infection in broiler chickens threatens public health and livestock production. In this study, we explored the effects of highly nutritious (crude protein 21.8%, metabolizable energy 3.16 Mcal/kg) and lowly nutritious (crude protein 18.1%, metabolizable energy 2.98 Mcal/kg) diets on S. Typhimurium infection by altering the intestinal morphology and environment in broiler chickens. The highly nutritious diet significantly increased the body weight gain and reduced feed conversion ratio on day 1 to 21 (P < 0.01). The highly nutritious diets promoted the intestinal villus height, crypt depth, and their ratio to improve the intestinal epithelial maturation (P < 0.05). Highly nutritious diets significantly increased the expression of claudin-1, occludin, and NF-κB genes in the intestinal epithelium on the days of 14 and 21 (P < 0.05). S. Typhimurium activated the expression of TLR4, MyD88, and NF-κB genes to cause an inflammatory response. The S. Typhimurium can increase the activity of myeloperoxidase, which cause an inflammatory response. The S. Typhimurium significantly reduced the diversity indexes of the ileal microbiota (P < 0.05), increased the abundance of Cyanobacteria which can synthesize toxins. The highly nutritious diet group challenged with S. Typhimurium can increase the abundance of Lactobacillus in the ileum, which lead to improved intestinal health (P < 0.05). It is concluded that increasing the nutritional level of dietary is beneficial to improve the resistance to S. Typhimurium infection by altering the intestinal bacterial community.